Characterizing mental health/addictions and assault visits in the year prior to death: a population-based linked cohort study of homicide victims - O'Neill, Meghan; Buajitti, Emmalin; Donnelly, Peter D; Kornas, Kathy; Rosella, Laura (International Journal of Population Data Science, 2021)
Introduction Homicide is an important cause of death for older youth and adult Canadians; however, little is known about health care use prior to death among this population. Objectives To characterise health care use for mental health and addictions (MHA) and serious assault (herein referred to assault) one year prior to death among individuals who died by homicide in Ontario, Canada using linked mortality and health care utilisation data. Methods We report rates of health care use for MHA and assault in the year prior to death among all individuals 16 years and older in Ontario, Canada, who died by homicide from April 2003 to December 2012 (N=1,541). Health care use for MHA included inpatient stays, emergency department (ED) visits and outpatient visits, whereas health care use for assault included only hospital-based care (ED visits and inpatient stays). Sociodemographic characteristics and health care utilisation were examined across homicide deaths, stratified by sex. Results Overall, 28.5% and 5.9% of homicide victims sought MHA and assault care in the year prior to death, respectively. A greater proportion of females accessed care for MHA, whereas a greater proportion of males accessed assault-related health care. Males were more likely to be hospitalised following an ED visit for a MHA or assault related reason, in comparison to females. The most common reason for a MHA hospital visit was for substance-related disorders. We found an increase over time for hospital-based visits for assault prior to death, a trend that was not observed for MHA-related visits. Conclusions A large proportion of homicide victims interacted with the health care system for MHA or assault in the year prior to death. An increase in hospital-based visits for assault-related reasons prior to death was observed. These trends may offer insight into avenues for support and prevention for victims of homicide.